Petrological and Geochemical Study of Dolomitization in the Middle Jurassic Rock of AL-Querdaha Sheet - إبراهيم, أحلام; سلمان , ندى; منصور , ربيع (Latakia University Journal -Basic Sciences Series, 2020)
This study was carried out in AL-Querdaha Sheet, in the north and center of the coastal chain in northwestern Syria, in order to determine the spread and model of dolomitization in the region due to its importance (scientific and economic), three stratigraphic sections were raised in the north, center and south of the study area and take rock samples from them, one hundred microscopic slides were prepared for study with of polarizing microscope before and after staining with Alizarin Red, Potassium fresianide solution to detect Ferroan dolomite and calcite, XRF analysis was also performed on the rock samples to determine the percentage of major oxides in them, the study showed that the dolomitization in the region follow seepage- reflux model, it also showed that the northern part of the study area is free from any trace of the dolomitization, while it is spreading in the center and south of the region, and showed There are four types of zones around the dolomite crystals from the inside out:1-dolomite zones, 2-calcite zones, 3- ferroan dolomite zones, 4- hematite zones, the presence of the zones reflects several stages of the Diaginiese, starting with the formation of the dolomitic zones due to the increase in the ratio Mg/Ca, which leads to the replacement of Ca 2+ by Mg2+in the initial calcite crystals and the formation of early dolomite crystals.